2019
DOI: 10.12659/msm.915909
|View full text |Cite
|
Sign up to set email alerts
|

Rumen-Protected 5-Hydroxytryptophan Improves Sheep Melatonin Synthesis in the Pineal Gland and Intestinal Tract

Abstract: Background Based on the extensive biological effects of melatonin (MLT), it is beneficial to increase the MLT content in the bodies of animals at a specific physiological stage. This study was conducted to investigate the effect of a diet supplemented with rumen-protected (RP) 5-hydroxytryptophan (5-HTP) on the pineal gland and intestinal tract MLT synthesis of sheep. Material/Methods Eighteen Kazakh sheep were assigned randomly to 3 diet groups: control group (CT, corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This observation is consistent with previous reports. Studies have shown when sheep were orally given 111–222 mg/kg LBW (equivalent 5-HTP 50–100 mg/kg LBW) rumen-protected 5-HTP, it increased their jejunum, ileum, cecum, and colon mucosa and plasma 5-HTP concentrations; however, the dose they used was much higher than those used in this study [ 36 , 39 , 40 ]. It has been reported that high dose of 5-HTP intravenous administration (over 300 mg/d) leads to animal developing poisoning symptoms similar to 5-HT-induced toxicity [ 41 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This observation is consistent with previous reports. Studies have shown when sheep were orally given 111–222 mg/kg LBW (equivalent 5-HTP 50–100 mg/kg LBW) rumen-protected 5-HTP, it increased their jejunum, ileum, cecum, and colon mucosa and plasma 5-HTP concentrations; however, the dose they used was much higher than those used in this study [ 36 , 39 , 40 ]. It has been reported that high dose of 5-HTP intravenous administration (over 300 mg/d) leads to animal developing poisoning symptoms similar to 5-HT-induced toxicity [ 41 ].…”
Section: Discussionmentioning
confidence: 73%
“…While if the dose of 5-HTP was under 50 mg/d, no adverse effects were observed. Based on the results mentioned above, in the current study, 5-HTP doses selected were 10 and 50 mg/d which is 50–100 times lower than that used by Zhao et al [ 36 , 39 ]. This difference may be due to the bioavailability of 5-HTP by the different delivery methods.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In sheep, the administration of 5-HTP substantially increases serum melatonin through a marked increase in pineal 5-HT and its metabolites, including N -acetylserotonin [ 126 ], whereas during the natural light period, a promotion of melatonin synthesis in the pineal gland and intestinal tract was found in rumen-protected 5-HTP [ 127 ]. In fetal lambs in late gestation, systemic infusion of 5-HTP during normoxia greatly increases the incidence of fetal breathing movements [ 128 ].…”
Section: Physiological Effects Of 5-htpmentioning
confidence: 99%
“…In addition to serotonin, melatonin production may also increase when sows are supplemented with tryptophan. In sheep, tryptophan supplementation (222 mg/kg BW) increased melatonin production compared to no supplementation [ 18 ]. Melatonin has been shown to decrease oxidative stress, which indirectly increases umbilical blood flow, increasing nutrient and oxygen supply to the developing fetus.…”
Section: Introductionmentioning
confidence: 99%